Herpetofauna roadkills on Langkawi Island, Peninsular Malaysia: the influence of landscape and season on mortality distribution - Norshaqinah Ayob,; Muzneena Ahmad Mustapha,; Juliana Senawi,; Norhayati Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2020)
We examined the spatiotemporal variation of herpetofauna roadkills on roadways in Langkawi Island. A total of 131 roadkills were recorded. The species that exhibited greater mortality was Varanus nebulosus (n=72). There was a significant difference in herpetofauna mortality between dry and wet seasons (t(11) =-2.330, p=0.04, <0.05). The spatial pattern was described by using kernel density estimation. Four collision hotspots were concentrated at the west side of the island, adjacent to vegetation area and forest reserve. Species characteristics, road proximity to the forested area, vegetation cover and traffic volume may influence the high rate of roadkills found. Installation of warning signs, speed restrictions and temporary road closings could reduce traffic accident and significantly reduce mortalities. The study represents a significant improvement over previous research on the island by implementing hotspot analysis. We would suggest analysing habitat suitability and connectivity to increase the ability to predict the location of roadkill hotspots.